Remittances and Economic Growth: Evidence from Ethiopia, Kenya, and Uganda - Zerihun, Mulatu F (African Human Mobility Review, 2021)
The purpose of this study is to analyze the possible effect of international remittances on the economic growth in three selected economies of Intergovernmental Authority on Development (IGAD) member countries, namely, Ethiopia, Kenya, and Uganda. Remittance inflows have emerged as a key link between human mobility and development. However, empirical findings on the nexus between remittances and economic growth are either conflicting or at most mixed. This paper explores the effects of remittances from international migration inflows on the economic growth of three IGAD member countries. The study uses quantitative analysis that encompasses the above-mentioned countries using the World Bank’s annual data from 1990 to 2017. The novelty of this study is that it uses different approaches to solicit the short-run and the long-run nexus between economic growth and remittance flow. The pooled estimation result from fully modified least squares (FMOLS) shows that the logarithm of remittances impacts the dependent variable, economic growth, positively but not statistically significant. The Kao panel residual cointegration test shows that the null hypothesis is not sufficiently supported by the data. There is a statistically significant long-run relationship between the variables in the series.